Analisis Matematis dan Ekonomis Penggunaan Metanol dan Etanol pada Kompor “hd” - Dwi Priyo Utomo (Department Industrial Engineering, University of Muhammadiyah Malang, 2010)
High energy requirements result in increased fuel prices. It is quite an impact on all sectors mainly engaged in the business world, because the cost of increasing production without increasing the purchasing power offset market. One effort that can be done is the use of alternative fuels economical. The question is bioethanol fuel, methanol and ethanol that requires an appropriate stove design for the fuel. To determine the level of fuel efficiency is needed stove heaters called “HD”. The purpose of this study was to determine the economic value of fuel use of methanol and ethanol on the stove “HD”, particularly in heating the chicken coop. The me thod used to determine the level of efficiency in the use of methanol and ethanol fuel is amethod of boiling water. Measurements carried out on several parameters, namely: the volume of water in a saucepan, water temperature before it is heated, the use of heavy fuel, fuel density, temperature difference, the total energy absorbed, the amount of energy absorbed, the minimum energy required, and the amount of water boiled. Based on mathematical analysis,concluded that the use of fuel ethanol has a boiling speeds higher than methanol. Although the time of boiling methanol fuel longer, but the use of methanol fuel is more economical. The use of methanol fuel content of 85% is more economical because of savings significantly which is Rp 544,984, 00 for broiler farms per 1000 larvae in one period of 40 days.